Jack Welch and the 4E's of Leadership : How to Put GE's Leadership Formula to Work in Your Organization - Krames, Jeffrey A. (New Delhi McGraw-Hil, 2006)
Beyond the nuts and bolts of the 4e model, this book outlines a step-by-step blueprint anyone can follow to stock an organization with performance-ready leaders and leaders-in-training.
Include Index and Notes
Keywords: Industrial management -- Leadership